Hereditary xanthinuria is not so rare disorder of purine metabolism - Sebesta, I.; Stiburkova, B.; Krijt, J. (Nucleosides, nucleotides & nucleic acids, 2018)
Hereditary xanthinuria (type I) is caused by an inherited deficiency of the xanthine oxidorectase (XDH/XO), and is characterized by very low concentration of uric acid in blood and urine and high concentration of urinary xanthine, leading to urolithiasis. Type II results from a combined deficiency of XDH/XO and aldehyde oxidase. Patients present with hematuria, renal colic, urolithiasis or even acute renal failure. Clinical symptoms are the same for both types. In a third type, clinically distinct, sulfite oxidase activity is missing as well as XDH/XO and aldehyde oxidase. The prevalence is not known, but about 150 cases have been described so far. Hypouricemia is sometimes overlooked, that´s why we have set up the diagnostic flowchart. This consists of a) evaluation of uric acid concentrations in serum and urine with exclusion of primary renal hypouricemia, b) estimation of urinary xanthine, c) allopurinol loading test, which enables to distinguish type I and II; and finally assay of xanthine oxidoreductase activity in plasma with molecular genetic analysis. Following this diagnostic procedure we were able to find first patients with hereditary xanthinuria in our Czech population. We have detected nine cases, which is one of the largest group worldwide. Four patients were asymptomatic. All had profound hypouricemia, which was the first sign and led to referral to our department. Urinary concentrations of xanthine were in the range of 170-598 mmol/mol creatinine (normal < 30 mmol/mol creatinine). Hereditary xanthinuria is still unrecognized disorder and subjects with unexplained hypouricemia need detailed purine metabolic investigation.